2000
DOI: 10.1161/01.hyp.36.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise and Weight Loss on Mental Stress–Induced Cardiovascular Responses in Individuals With High Blood Pressure

Abstract: Abstract-The purpose of this study was to determine the effects of exercise and weight loss on cardiovascular responses during mental stress in mildly to moderately overweight patients with elevated blood pressure. Ninety-nine men and women with high normal or unmedicated stage 1 to stage 2 hypertension (systolic blood pressure 130 to 179 mm Hg, diastolic blood pressure 85 to 109 mm Hg) underwent a battery of mental stress tests, including simulated public speaking, anger recall interview, mirror trace, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 33 publications
2
38
0
3
Order By: Relevance
“…Increasing fitness is likely one of the most potent interventions for restoring A/C balance and can improve well-being. Long-term exercise can decrease cortisol and increase DHEA, GH, and IGF-1, 154 and is associated with reduced cortisol reactivity 155 and cardiovascular reactivity to acute stress, 156 as well as reduced anxiety 157 and depressive symptoms. 158 Psychosocial interventions have been effective in improving A/C balance.…”
Section: F1 Psychological/behavioral Interventionsmentioning
confidence: 99%
“…Increasing fitness is likely one of the most potent interventions for restoring A/C balance and can improve well-being. Long-term exercise can decrease cortisol and increase DHEA, GH, and IGF-1, 154 and is associated with reduced cortisol reactivity 155 and cardiovascular reactivity to acute stress, 156 as well as reduced anxiety 157 and depressive symptoms. 158 Psychosocial interventions have been effective in improving A/C balance.…”
Section: F1 Psychological/behavioral Interventionsmentioning
confidence: 99%
“…Previous studies have suggested that aerobic exercise training may reduce type A behaviors and attenuate cardiovascular stress responses. 29 In a RCT investigating the impact of exercise and weight loss on blood pressure in a sample of overweight, hypertensive individuals, Georgiades and colleagues 30 found that exercise was effective in reducing resting and stress-induced blood pressure levels, particularly when combined with a behavioral weight loss program. In addition, exercise combined with a weight loss program was found to decrease hemodynamic stress responses for this population to those levels targeted by pharmacologic antihypertensive treatments.…”
Section: Pulmonary Diseasementioning
confidence: 99%
“…For example, insulin-resistant adults exhibited exaggerated TPR reactivity to behavioral stress tasks, but only during high-carbohydrate intake [60]. Weight-loss programs have also been shown to reduce TPR [61], although it is not clear whether this is an effect of weight loss per se, or real effect of a more nutritious diet. Others have measured TPR to document the acute vascular effects of nutritional supplements.…”
Section: Effects Of Diet On Systemic Hemodynamicsmentioning
confidence: 99%